2015
DOI: 10.5194/hess-19-1501-2015
|View full text |Cite
|
Sign up to set email alerts
|

Scoping a field experiment: error diagnostics of TRMM precipitation radar estimates in complex terrain as a basis for IPHEx2014

Abstract: Abstract.A diagnostic analysis of the space-time structure of error in quantitative precipitation estimates (QPEs) from the precipitation radar (PR) on the Tropical Rainfall Measurement Mission (TRMM) satellite is presented here in preparation for the Integrated Precipitation and Hydrology Experiment (IPHEx) in 2014. IPHEx is the first NASA ground-validation field campaign after the launch of the Global Precipitation Measurement (GPM) satellite. In anticipation of GPM, a science-grade high-density raingauge ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…Warm orographic rains are thus likely to be underestimated by satellite observation (also Shige et al ). Duan et al () also investigated the precipitation radar QPE by the TRMM in the southern Appalachian Mountains and found that precipitation of small‐scale systems and isolated deep convection tends to be underestimated due to spatial averaging at the radar resolution. These explanations could also be applied to the underestimated precipitation maxima over the complex topography in the western US.…”
Section: Biases In the Diurnal Cycle Of Precipitationmentioning
confidence: 99%
“…Warm orographic rains are thus likely to be underestimated by satellite observation (also Shige et al ). Duan et al () also investigated the precipitation radar QPE by the TRMM in the southern Appalachian Mountains and found that precipitation of small‐scale systems and isolated deep convection tends to be underestimated due to spatial averaging at the radar resolution. These explanations could also be applied to the underestimated precipitation maxima over the complex topography in the western US.…”
Section: Biases In the Diurnal Cycle Of Precipitationmentioning
confidence: 99%
“…, n tot is the number of time steps (total of N tot time steps), p is the precipitation intensity at a particular grid cell, and r is the aggregated spatial resolution (0.18 or 0.258). Rainfall detection is assessed by three categorical error scores: the accuracy index (ACC; Duan et al 2015), the probability of detection (POD), and the false alarm ratio (FAR):…”
Section: B Evaluation Metricsmentioning
confidence: 99%
“…For convenience, rainfall amounts for these three datasets are denoted as P (station), P (TRMM), and P (GBT), respectively. As noted by Duan et al (2015), the TRMM PR exhibits terrain bias. Thus, the TRMM PR and GBT data are calibrated with the area-mean station rainfall over three ranges of altitude: 0-100, 100-500, and 500-1000 m in areas 1-3, respectively, shown in the left-hand column of Fig.…”
Section: Rainfall Estimation Over the Taipei Basinmentioning
confidence: 99%
“…Using only station data over the stationdense area to estimate the area-mean rainfall enables us to use this area-mean rainfall to calibrate TRMM rainfall and GBT rainfall proxy. Duan et al (2015) noted that calibration of rainfall proxy with satellite observations could be affected by orography. Therefore, the mountain height within the basin is divided into three ranges: 0-100, 100-500, and 500-1000 m. To save space, a detailed calibration procedure for both TRMM rainfall and GBT rainfall proxy data over the entire analysis domain (encircled by the red line in Fig.…”
Section: ) Identification Of Ts and No-ts Days And Other Weather Symentioning
confidence: 99%